2017
DOI: 10.1002/14651858.cd007649.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Certolizumab pegol (CDP870) for rheumatoid arthritis in adults

Abstract: This is the published version of the paper.This version of the publication may differ from the final published version. Permanent repository link:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 83 publications
1
33
0
Order By: Relevance
“…Our systematic review did not provide ample evidence that would support a differential risk of serious infection among available biologic agents . Because avoiding infection was significantly more important to patients than flares in the postoperative period, the Panel did not support separating biologic agents regarding infection risk in the perioperative period until further studies clarify and establish differences in risk . The literature review also revealed that the risk of postoperative infection complications after total joint arthroplasty (TJA) was increased in patients with RA nearly 2‐fold, and deep infection complications increased by 1.5‐fold ; in SLE, overall postoperative complications were increased 1.3‐fold, and septicemia by 2‐fold , although medication use at the time of surgery was not always reported.…”
Section: Results/recommendationsmentioning
confidence: 89%
See 2 more Smart Citations
“…Our systematic review did not provide ample evidence that would support a differential risk of serious infection among available biologic agents . Because avoiding infection was significantly more important to patients than flares in the postoperative period, the Panel did not support separating biologic agents regarding infection risk in the perioperative period until further studies clarify and establish differences in risk . The literature review also revealed that the risk of postoperative infection complications after total joint arthroplasty (TJA) was increased in patients with RA nearly 2‐fold, and deep infection complications increased by 1.5‐fold ; in SLE, overall postoperative complications were increased 1.3‐fold, and septicemia by 2‐fold , although medication use at the time of surgery was not always reported.…”
Section: Results/recommendationsmentioning
confidence: 89%
“…This recommendation was based on evidence that was rated down in quality for indirectness, as no RCTs were performed in patients undergoing THA or TKA. We abstracted data from a systematic review of literature that included systematic reviews and meta‐analyses of biologic agents versus placebo (and occasionally versus control treatment including nonbiologic DMARDs) in nonsurgical patients, which revealed that the risk of serious infections was increased with biologic agents, with most odds/hazards/risk ratios ∼1.5 (range 0.61–8.87) and a higher risk of serious adverse events with most odds/hazards/risk ratios ∼1.5 (range 0.33–2.54) . Our systematic review did not provide ample evidence that would support a differential risk of serious infection among available biologic agents .…”
Section: Results/recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the initial stage of RA (the first 6 months of symptoms) and whenever the disease presents with significant inflammatory activity, follow-up should be performed monthly to allow dosage adjustment or changes in medication for disease management. The efficacy (ACR50 response) of methotrexate (MTX) monotherapy is similar to that of bDMARD monotherapy, except for tocilizumab, which was more effective than MTX [16][17][18][19][20][21][22][23].…”
Section: General Principlesmentioning
confidence: 99%
“…However, patients using bDMARD in sustained remission may receive a bDMARD dose reduction or dose interval increase. Although disease reactivation may occur in some cases, disease control is usually reestablished with the return to the previous dose schedule (moderate to low evidence) [19,23,104,105,114,133]. In cases of complete and sustained remission (at least 6 months), gradual and careful treatment withdrawal may be attempted in the following sequence: first NSAIDs, followed by corticosteroids, and bDMARD or tsDMARD, but maintaining the use of csDMARD.…”
Section: Gradual Reduction Of Medication Dose and Treatment Discontinmentioning
confidence: 99%